Peran Badan Usaha Milik Desa (BUMDes) Dalam Mengembangkan Usaha Ketahanan Pangan di Desa Hilifalawu Kecamatan Huruna Kabupaten Nias Selatan - Halawa, Fiteriman; Lase, Fatiani; Harefa, Hendrikus O. N.; Harefa, Amstrong (Innovative: Journal Of Social Science Research, 2024)
This study aims to determine the role and constraints and efforts to overcome the constraints of village-owned enterprises (BUMDes) in developing food security businesses, in Hilifalawu Village, Huruna District, South Nias Regency. This study uses a descriptive approach with a qualitative method, with the research instrument being the researcher himself who collects data through observation, interviews, and documentation using a cellphone. The results of the research and discussion show that: First, BUMDes in developing food security businesses plays an active role in efforts to improve the quality of people's lives, strengthen the people's economy as the basis for the strength and resilience of the local economy of Hilifalawu Village. Second, the constraints of BUMDes in developing food security businesses are minimal capital, lack of human resources, limited marketing, infrastructure and low education and training. Third, efforts to overcome the constraints of BUMDes in developing food security businesses are providing education and training, providing capital to the community, providing farming equipment, promoting crops, and proposing plans for infrastructure development to the local government.